2018
DOI: 10.1001/jamaoto.2017.2618
|View full text |Cite
|
Sign up to set email alerts
|

Indirect vs Direct Voice Therapy for Children With Vocal Nodules

Abstract: clinicaltrials.gov Identifier: NCT01255735.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 30 publications
0
44
0
2
Order By: Relevance
“…Instead, current models (i.e., [13]) suggest focusing on motor learning principles and 'direct' therapy. In a randomized clinical trial that evaluated the 'direct' versus 'indirect' voice therapy in CwVN, improvements were seen from both therapies [28]. Yet, when evaluating the difference in outcome measures for 'direct' as compared to 'indirect' therapy across age, larger effect sizes were seen in children over eight years of age.…”
Section: Clinical Implications For Voice Therapy In Cwvnmentioning
confidence: 98%
See 4 more Smart Citations
“…Instead, current models (i.e., [13]) suggest focusing on motor learning principles and 'direct' therapy. In a randomized clinical trial that evaluated the 'direct' versus 'indirect' voice therapy in CwVN, improvements were seen from both therapies [28]. Yet, when evaluating the difference in outcome measures for 'direct' as compared to 'indirect' therapy across age, larger effect sizes were seen in children over eight years of age.…”
Section: Clinical Implications For Voice Therapy In Cwvnmentioning
confidence: 98%
“…Consistent with this timeframe, the current study also showed differences between younger and older children in auditory discrimination abilities. Therefore, if children in the clinical trial [28] over the age of eight had adult-like discrimination abilities, this may have provided them with an increased ability to hear subtle differences in voices. This ability could subsequently allow them to benefit more from direct therapy.…”
Section: Clinical Implications For Voice Therapy In Cwvnmentioning
confidence: 99%
See 3 more Smart Citations